Resilience stories : individualized tales of a metanarrative - Mahdiani, Hamideh (Lettre (Transcript (Firm)), 2021)
Be resilient! Today, we hear this line in almost any context. The term resilience is among the most repeated buzzwords. But why, simply, do we need to be resilient? Hamideh Mahdiani presents answers to this question by challenging a reductionistic understanding of resilience from single disciplinary perspectives; by questioning the dominance of life sciences in defining an age-old concept; and by problematizing the neglected role of life writing in fostering resilience. In so doing, through a multidisciplinary frame of reference, the book works with various examples from life writing and life sciences, and testifies to the focal role of narrative studies in resilience research.